2020
DOI: 10.31687/saremnms.20.0.25
|View full text |Cite
|
Sign up to set email alerts
|

El perezoso de dos dedos (Choloepus hoffmanni) en Honduras: distribución, historia natural y conservación

Abstract: RESUMENCholoepus hoffmanni Peters, 1858 ha sido poco estudiada en Honduras, el país más septentrional de su distribución. Presentamos algunas observaciones sobre su distribución, dieta, comportamiento y amenazas en el país. Los registros confirmados para la especie en Honduras incluyen 11 documentados con anterioridad y seis nuevos, presentados aquí. De los 17, solamente seis corresponden a observaciones directas, uno de los cuales extiende la distribución global conocida hacia el norte de Honduras (Los Naranj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The activity of two-toed sloths is predominantly nocturnal. They are awake from 9 p.m. to 4 a.m., with activity peaks between 9-10 p.m. and 2-3 a.m. (Sunquist and Montgomery 1973;Mosquera et al, 2019;Martínez et al 2020). Thus, we conducted follow-up every day after release, from 5:30-6:00 p.m. to 4-6 a.m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of two-toed sloths is predominantly nocturnal. They are awake from 9 p.m. to 4 a.m., with activity peaks between 9-10 p.m. and 2-3 a.m. (Sunquist and Montgomery 1973;Mosquera et al, 2019;Martínez et al 2020). Thus, we conducted follow-up every day after release, from 5:30-6:00 p.m. to 4-6 a.m.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we conducted follow-up every day after release, from 5:30-6:00 p.m. to 4-6 a.m. Through continuous direct observation and annotations every 30 min, the sloth's movements, interactions and vocalizations were recorded (Martínez et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The first specimens were mentioned by Gamero (1978) and McCarthy et al (1999). Martínez et al (2020b) McCarthy et al (1999) reported specimens in the National Museum of Natural History (USNM) collection and located two B. variegatus skins with skulls (USNM 21010, male; 21011, female) that had been obtained by Perry on 1 June and 9 November 1891, respectively, in Patuca, Honduras. This locality may refer to the coastal settlement of Patuca (15°50'N, 84°17'W) or Barra Patuca at Punta Patuca (15°51'N, 84°18'W) (McCarthy et al, 1999).…”
Section: Figure 2 Previous and New Records Of Bradypus Variegatus In Hondurasmentioning
confidence: 99%
“…For example, half of the known records of Ch. hoffmanni correspond to confiscated animals or specimens that are located in ex situ conservation centers, which probably have been confiscated from traffickers (Martínez et al, 2020b). It is therefore possible that these activities are affecting the wild sloth populations, and especially those of Ch.…”
Section: Intentional Fires According To the Iucn Redmentioning
confidence: 99%
“…Martínez et al (2020b) McCarthy et al(1999) reported specimens in the National Museum of Natural History (USNM) collection and located two B. variegatus skins with skulls (USNM 21010, male; 21011, female) that had been obtained by Perry on 1 June and 9 November 1891, respectively, in Patuca, Honduras. This locality may refer to the coastal settlement of Patuca (15°50'N, 84°17'W) or Barra Patuca at Punta Patuca (15°51'N, 84°18'W) (McCarthy et al, 1999).…”
mentioning
confidence: 99%